2019
DOI: 10.5400/jts.2019.v24i3.141-148
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Tillage and in situ Mulch Increasing the Population and Biomass of Earthworms Under Mung Bean Cultivation on Ultisol Soil

Abstract: Earthworms are important soil biota that can be used as  an indicator of soil fertility. Soil tillage systems and application of organic mulch will affect the activity of earthworms. This research was aimed to study the effect of tillage systems and the application of in situ mulch, and their interactions on the population and the biomass of earthworms. The study was conducted from April to July 2017 at the Integrated Field Laboratory, Faculty of Agriculture, University of Lampung. The study was arranged in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…It was probably due to the higher CA soil moisture [19,53,54] than in the TA, 10.89 ± 0.72 and 9.93 ± 0.51%, respectively (Figure 4), and cover crop in the CA presented 0.24 ± 0.06 kg m −2 of Desmodium sp., which served as a food source for earthworms [19]. Analogously, the number of earthworms m −2 reported by McInga et al, Nurul Aini et al, and Birkás et al [18,53,55] in the CA soils was higher by 24, 17, and 52 earthworms m −2 , respectively, than in the TA soils, probably due to the elimination of tillage and the presence of crop stubble on the soil, conditions that provided a suitable abiotic environment for the development of earthworms [54].…”
Section: Earthworm Populationmentioning
confidence: 98%
See 1 more Smart Citation
“…It was probably due to the higher CA soil moisture [19,53,54] than in the TA, 10.89 ± 0.72 and 9.93 ± 0.51%, respectively (Figure 4), and cover crop in the CA presented 0.24 ± 0.06 kg m −2 of Desmodium sp., which served as a food source for earthworms [19]. Analogously, the number of earthworms m −2 reported by McInga et al, Nurul Aini et al, and Birkás et al [18,53,55] in the CA soils was higher by 24, 17, and 52 earthworms m −2 , respectively, than in the TA soils, probably due to the elimination of tillage and the presence of crop stubble on the soil, conditions that provided a suitable abiotic environment for the development of earthworms [54].…”
Section: Earthworm Populationmentioning
confidence: 98%
“…It was probably due to the higher CA soil moisture [19,53,54] than in the TA, 10.89 ± 0.72 and 9.93 ± 0.51%, respectively (Figure 4), and cover crop in the CA presented 0.24 ± 0.06 kg m −2 of Desmodium sp., which served as a food source for earthworms [19]. Analogously, the number of earthworms m −2 reported by McInga et al, Nurul Aini et al, and Birkás et al [18,53,55] in the CA soils was higher by 24, 17, and 52 earthworms m −2 , respectively, than in the TA soils, probably due to the elimination of tillage and the presence of crop stubble on the soil, conditions that provided a suitable abiotic environment for the development of earthworms [54]. The earthworm population with hydraulic conductivity (Ks) and bulk density (Bd) showed a negative and positive correlation (r = −0.93 and r = 0.43), respectively, probably due to a certain population of "soil compacting earthworm species" such as Millsonia anomala Omodeo and Vaillaud, normally found in the Peruvian Amazon [51], which could increase Bd and decrease Ks.…”
Section: Earthworm Populationmentioning
confidence: 98%
“…The presence of earthworms will also fertilize the soil, however some researchers report that earthworms are easy to change with practice of soil tillage [4] As a bioindicators, the abundance and biomass of organisms in soils, especially earthworms, are strongly influenced by soil management. In general trend, conservation tillage, as consist of no tillage and minimum tillage, tends to increase abundance of earthworm [5], [6]. The results of Sembiring [7] tillage system had a significant effect on the population and earthworms biomass in the land after fallowing for more than 10 years concluded that the abundance and biomass of earthworms in no-tillage and minimum tillage treatments compared to intensif tillage.…”
Section: Introductionmentioning
confidence: 99%